No serological evidence for Zika virus infection and low specificity for anti-Zika virus ELISA in malaria positive individuals among pregnant women from Madagascar in 2010. - Norbert Georg Schwarz; Eva Mertens; Doris Winter; Oumou Maiga-Ascofaré; Denise Dekker; Stephanie Jansen; Dennis Tappe; Njary Randriamampionona; Jürgen May; Raphael Rakotozandrindrainy; Jonas Schmidt-Chanasit (PLoS ONE)
It was previously reported that a malaria infection may interfere with the specificity of a commercial ELISA test against Zika virus (ZIKV). We analyzed 1,216 plasma samples from healthy, pregnant women collected in two sites in Madagascar in 2010 for ZIKV antibodies using a commercial ELISA and for Plasmodium infection by PCR. This screen revealed six putative ZIKV-positive samples by ELISA. These results could not be confirmed by indirect immunofluorescence assays or virus neutralization tests. Four of these six samples were also positive for P. falciparum. We noted that the frequency of malaria positivity was higher in ZIKV-ELISA positive samples (50% and 100% in the two study sites) than ZIKV-negative samples (17% and 10%, respectively), suggesting that malaria may have led to false ZIKV-ELISA positives.